Peripartum Physical and Behavioural Changes in Female Mithun (Bos frontalis) - AHMED, F A; BAISHYA, N; BUJARBARUA, K M; AKHTAR, F A (The Indian Journal of Animal Reproduction, 2023)
The prepartum physical changes observed in female mithun were edematous swelling of vulva, development of udder, engorgement of teats, relaxation of pelvic ligaments. and presence of mucus at vulva; and behavioural changrs included self isolation from rest of the herd, calm and quiet walking and preference of being in confinement. The behavioural signs of first stage of parturition were observed as restlessness manifested by rapid change in position in all female animals. During the second stage of parturition all the animals showed severe abdominal straining and frequently raised their tails. All the animals delivered their fetus in lie down position. Just after delivery of the fetus the mother was busy with the new born.